Molecular identification of four Dunaliella strains from Ukraine via ITS2 marker - Fursova, K.; Horpynchenko, M.; Utevska, O.; Komarysta, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2026)
Species of the genus Dunaliella are model organisms in algal physiology and widely used in phycotechnologies for commercial production of bioactive compounds, particularly carotenoids (mainly β-carotene). Reliable species identification is challenging due to low morphological variability and the absence of distinct species-specific traits in Dunaliella. Common traits such as cell size, shape, and pigmentation are strongly influenced by environmental factors, often leading to misidentification in culture collections and complicating comparative and applied research. Molecular approaches have thus become essential for accurate species identification. However, molecular data on Dunaliella from Ukraine remain scarce. The internal transcribed spacer 2 (ITS2) region is particularly informative, combining conserved secondary structures with rapidly evolving primary sequences. This study performed molecular identification of four Dunaliella strains from the Cherniaev Herbarium MicroAlgae Culture Collection (CWU-MACC), V.N. Karazin Kharkiv National University, using the ITS2 marker. Species identification was performed based on sequence similarity and phylogenetic analysis. Among the four Ukrainian strains, only CWU-MACC-15 corresponded to D. salina, while the others, including CWU-MACC-16, previously identified as D. salina, were assigned to D. viridis. The ITS2 sequences of CWU-MACC-16 and CWU-MACC-20 were identical, whereas the Henichesk Lake isolate showed a minor ITS2 variation within D. viridis. These results provide a molecular basis for the taxonomy of Dunaliella strains from Ukraine and highlight the need for expanded sampling and additional molecular markers to further resolve species diversity and phylogenetic relationships.